Experimental study of urea-catalyzed microbial solution-based curing of fissured loess soil - Pan, Chaofan; Zhang, Chen; Ji, Tuo (Frontiers in Materials, 2025)
The ubiquitous vertical cracks in loess areas are one of the main factors that cause disasters in engineering projects, and the restoration of cracked loess is of great significance for disaster prevention. Microbial-induced calcium carbonate precipitation (MICP), as a green solidification method, is widely used in soil remediation. Microstructural changes in crack-free loess after solidification were analyzed using a scanning electron microscope, and the optimal grouting scheme of microbial solution catalyzed by urea was determined. Solidification tests were carried out on fractured loess with different openings, and the solidification effect of MICP was evaluated using the direct shear test. The results show that the surface contact between micro-aggregates and the contact area between soil particles increased greatly after MICP curing. Under the catalysis of urea, the amount of CaCO3 increased by 30%, which enhanced the strength of the soil on both sides of the fractured loess structural plane after solidification. It provides a solid experimental basis and detailed microscopic explanation for MICP strengthening fractured loess.